A Study on the Efficacy of ChatGPT-4 in Enhancing Students’ English Communication Skills - Ying Wang (SAGE Open)
Optimizing communication learning experiences for students is a promising development in English language education, enabled by ChatGPT-4, an artificial intelligence software that excels in customizing lessons to suit specific requirements, interests, and preferred modes of communication for each student. Given its critical role in enhancing students’ communication proficiency, students’ utilization and acceptance of ChatGPT can have a positive impact. However, limited evidence exists regarding the extent to which ChatGPT-4 enhances students’ English communication skills. This study investigates the potential influence of ChatGPT-4 in enhancing students’ English communication abilities, using an experiment with 68 undergraduate students from the Wuhan University of Engineering Science, China. Participants were randomly assigned to two distinct groups. One experimental group was assigned to use ChatGPT-4, whereas the control group received traditional teacher-led instructions. Additionally, a questionnaire was administered. The results revealed that the use of ChatGPT-4 contributed to the development of students’ English communication abilities. Furthermore, the students’ English communication abilities significantly changed after using ChatGPT-4. Overall, student acceptance of ChatGPT changed significantly after implementing ChatGPT-4; the impact of ChatGPT-4 on their English communication was remarkable, creating a sense of calm and comfort among students, which is highly beneficial for language learning. A multitude of suggestions and recommendations were provided.